Audit Sistem Informasi Penjualan Menggunakan Framework Cobit 5 Pada Umkm Cks - Nazwa Nurul Hafizah Rangkuti; Elsa Risqi Amalia; Melani Puspita Sari; Rahayu Arnanda (Modem : Jurnal Informatika dan Sains Teknologi., 2024)
: This study aims to evaluate the sales information system at UMKM CKS using the COBIT 5 framework. Initial observations revealed several issues, including an unresponsive user interface and a complicated check-out process. The audit results showed an average maturity level of 1.56 or 156%, indicating a Fully Achieved (F) status with a systematic approach. However, on the capability model scale, it is at level 1, which is the Performed Process. The conclusion of this research indicates that although the sales information system has been successfully implemented, there is a need for innovation and enhancement of consumer services, as well as better communication between the company and consumers to improve the effectiveness of the information system.